Computer Assisted Instruction & the ACTFL Proficiency Guidelines - Huhn, Christina (IALLT Journal of Language Learning Technologies, 2011)
The current study presents the results of one mixed-method analysis of theimplementation of communicative online activities into beginning Spanishclasses, their effects on class performance, and evaluation of the studentgeneratedwork from the online module. Results show that althoughstatistically there may be some doubt as to the effectiveness of an additionof a WebCT/Blackboard ® component into a beginning Spanish program,the environment did provide opportunities for students to demonstratelanguage proficiency. It is the analysis of student writing samplesgathered from the hybrid course, using a rubric based on the ACTFLWriting Proficiency Guidelines, that adds depth and breadth to the study.The article also addresses common issues that arise in traditionalanalyses of technology implementations, and suggests ways that theACTFL Writing Proficiency Guidelines can be useful in the evaluation ofstudent work in qualitative research.